Slow and noisy: developmental time and gene expression kinetics in big cells - Taylor, Alexandra, author; Mueller, Rachel, advisor; Prasad, Ashok, advisor; Hoke, Kim, committee member; Krapf, Diego, committee member (Colorado State University. Libraries, 2023)
Evolutionary increases in genome size, cell volume, and nuclear volume have been observed across the tree of life, with positive correlations documented between all three traits. It is well documented that developmental tempo slows as genomes, nuclei, and cells increase in size, yet the driving mechanisms are poorly understood. Meanwhile, the dramatic increases in cell volume seen across the tree of life pose interesting questions about a potential relationship between cell volume and stochastic noise at the single cell level, but this remains an underexplored area of research. To bridge these knowledge gaps, we use a mix of deterministic and stochastic, as well as species-specific and more general, models of the somitogenesis clock. In doing so, we explore the impact of changing intra-cellular gene expression kinetics induced by increasing genome size, nuclear volume, and cell volume on developmental tempo and gene expression noise. Results suggest that longer transcriptional and nuclear export times act to slow cell and developmental processes down as genome size and cell volume increase, and that "search processes" undergone by gene products within a cell become noisier with increasing volume. Analyses of stochastic model simulations and existing empirical data bring into question whether or not cell-autonomous oscillations can truly exist in the absence of cell-to-cell signaling.